A New Concert? Diplomacy for a Chaotic World. Issue 6 (1st November 2020) - Aall, Pamela; Crocker, Chester A.; Hampson, Fen Osler
Abstract : A new 'concert' diplomacy is needed to foster informal, minilateral constellations of relevant actors operating alongside formal institutions of global governance.